(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
In this article, the social justice, human well-being, rights and interests are provided in the system of social interests, universal aspects and democratic essence of the ideas and concepts to improve the society in this process are scientifically analyzed. Also, scientific and practical opinions on ensuring that a person is respected in society in all respects and fully developed are presented.